2002
DOI: 10.1021/jm025539h
|View full text |Cite
|
Sign up to set email alerts
|

Design and Pharmacology of N-[(3R)-1,2,3,4-Tetrahydroisoquinolinium- 3-ylcarbonyl]-(1R)-1-(4-chlorobenzyl)- 2-[4-cyclohexyl-4-(1H-1,2,4-triazol- 1-ylmethyl)piperidin-1-yl]-2-oxoethylamine (1), a Potent, Selective, Melanocortin Subtype-4 Receptor Agonist

Abstract: Synthetic and natural peptides that act as nonselective melanocortin receptor agonists have been found to be anorexigenic and to stimulate erectile activity. We report the design and development of 1, a potent, selective (1184-fold vs MC3R, 350-fold vs MC5R), small-molecule agonist of the MC4 receptor. Pharmacological testing confirms the food intake lowering effects of MC4R agonism and suggests another role for the receptor in the stimulation of erectile activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
126
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(132 citation statements)
references
References 27 publications
(63 reference statements)
5
126
0
1
Order By: Relevance
“…Our initial design was inspired by the common structural features between MC-4 receptor agonist, discovered by Merck, and fentanyl, a potent l opioid receptor agonist (Figure 1). 20 Both structures have a piperidine scaffold appended with aromatic moieties. Ligand 6 was designed by the replacement of the 4-cyclohexyl-4- We systematically modified ligand 6 and performed structure-activity relationship (SAR) studies at both recep-FIGURE 1 Ligands for structure-activity relationships study.…”
Section: Resultsmentioning
confidence: 99%
“…Our initial design was inspired by the common structural features between MC-4 receptor agonist, discovered by Merck, and fentanyl, a potent l opioid receptor agonist (Figure 1). 20 Both structures have a piperidine scaffold appended with aromatic moieties. Ligand 6 was designed by the replacement of the 4-cyclohexyl-4- We systematically modified ligand 6 and performed structure-activity relationship (SAR) studies at both recep-FIGURE 1 Ligands for structure-activity relationships study.…”
Section: Resultsmentioning
confidence: 99%
“…THIQ, which is significantly smaller (Fw=589.169), actually has a lower affinity than peptide ligands and even the 39-amino acid peptide ACTH (Fw=4541.11) is capable of migrating through the yeast cell wall and activating the MC4R. It is reported that THIQ has approximately the same affinity for MC4R as αMSH [24,37]. The lower activity in yeasts may be explained by instability of THIQ in yeast culture where the activation process takes a significantly longer time when compared to the classical cAMP experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The amino-acid sequence of the MC4 receptor shares considerable homology with that of other GPCRs for which drugs had already been identified, such as the ghrelin receptor, which binds growth-hormone secretagogue compounds (Bondensgaard et al, 2004). A directed screen of a library containing growth-hormone secretagogue compounds yielded a moderate potency (110 nM) MC4 receptor hit (Sebhat et al, 2002). Compounds elaborated from this initial lead are similar to the bioactive structure of the endogenous peptide agonist a-melanocyte-stimulating hormone and synthetic peptide analogues (Sebhat et al, 2002;Sun et al, 2004).…”
Section: Ligand Structure: Drug Development For Peptide Gpcrsmentioning
confidence: 99%
“…A directed screen of a library containing growth-hormone secretagogue compounds yielded a moderate potency (110 nM) MC4 receptor hit (Sebhat et al, 2002). Compounds elaborated from this initial lead are similar to the bioactive structure of the endogenous peptide agonist a-melanocyte-stimulating hormone and synthetic peptide analogues (Sebhat et al, 2002;Sun et al, 2004). This information was used to guide further medicinal chemistry efforts to optimize small molecule potency for the MC4 receptor.…”
Section: Ligand Structure: Drug Development For Peptide Gpcrsmentioning
confidence: 99%